Does Physeal Preservation Matter? Patient-Reported Outcomes After Physeal-Sparing Versus Transphyseal Anterior Cruciate Ligament (ACL) Reconstruction in Pediatric Patients: A Systematic Review and Meta-Analysis - Mohammed Al-Rumaih; Ali Al-Ghufaily; Fares Al-Marek; Abdulrahman Al-Otaibi; Saleh Al-Saifi; Sasha Carsen; Donald Kephart; Bogdan Matache; Waleed Kishta (Osteology, 2026)
Background/Objectives: ACL injuries in skeletally immature patients present a unique surgical challenge, with ongoing debate regarding the optimal reconstruction technique relative to the open physis. Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines, searching PubMed/MEDLINE, Cochrane Library, and Google Scholar. Twenty-two studies (n = 1036 patients; 598 physeal-sparing, 438 transphyseal) were included. The evidence base consisted predominantly of non-randomized retrospective studies. Patient-reported outcomes, return-to-sport rates, growth disturbances, graft failure, and reoperation rates were pooled using a random-effects model. Results: Pooled IKDC scores were 95.14 (95% CI: 93.81–96.50) for physeal-sparing and 96.17 (95% CI: 93.98–98.42) for transphyseal reconstruction, with no significant between-group difference (p = 0.436). Lysholm scores were 95.56 versus 93.04 (p = 0.075), and Tegner scores were 6.39 versus 7.08 (p = 0.366), respectively, with no statistically significant differences. KOOSs also showed no significant difference (96.19 vs. 96.00; p = 0.948). The pooled return-to-sport rate was higher following transphyseal reconstruction than physeal-sparing reconstruction (97.8% vs. 93.9%; p = 0.034). Growth disturbances were more frequently reported in the physeal-sparing group (5.1% vs. 1.4%; p = 0.008). Graft failure (5.8% vs. 8.4%; p = 0.144) and reoperation rates (13.5% vs. 13.8%; p = 0.906) were comparable between techniques. Conclusions: Both techniques yielded comparable functional outcomes across major PROMs. Transphyseal reconstruction was associated with a higher pooled return-to-sport rate in the included studies, whereas physeal-sparing reconstruction was associated with a higher incidence of reported growth disturbances. However, these findings should be interpreted cautiously given that the evidence base consisted predominantly of non-randomized retrospective studies and was subject to potential confounding and other sources of bias.